The anti-oxidation related bioactive materials for intervertebral disc degeneration regeneration and repair - Yingjie Mai; Siying Wu; Penghui Zhang; Ningning Chen; Jun Wu; Fuxin Wei (Bioactive Materials)
Abstract:: Intervertebral disc degeneration (IVDD) is a prevalent chronic spinal condition characterized by the deterioration of the intervertebral discs (IVD), leading to structural damage and associated pain. This degenerative process is closely linked to oxidative stress injury, which plays a pivotal role in its onset and progression. Oxidative stress in IVDD results from the excessive production of reactive oxygen species (ROS) and impaired ROS clearance mechanisms, disrupting the redox balance within the intervertebral disc. Consequently, oxidative stress contributes to the degradation of the extracellular matrix (ECM), promotes cell apoptosis, and exacerbates disc tissue damage. Current treatment options for IVDD face significant challenges in effectively alleviating the oxidative stress-induced damage and facilitating disc tissue repair. However, recent advancements in biomaterials have opened new avenues of hope for IVDD treatment by addressing oxidative stress. In this review, we first provide an overview of the pathophysiological process of IVDD and explore the mechanisms and pathways associated with oxidative stress injury. Then, we delve into the current research on antioxidant biomaterials employed in the treatment of IVDD, and outline the advantages and limitations of hydrogel, nanomaterials, polyphenol and inorganic materials. Finally, we propose the future research direction of antioxidant biomaterials in IVDD treatment. The main idea of this review is shown in Scheme 1.